Effectiveness of clown intervention for pain relief in children: A systematic review and meta‐analysis. Issue 21 (5th January 2022) - Ding, Yiwen; Yin, Huiru; Wang, Shuo; Meng, Qiuyan; Yan, Mingli; Zhang, Yining; Chen, Li
Abstract: Background: Pain is common in children receiving medical procedures, and there is a lack of adequate awareness and management. In addition, children who undergo medical procedures involving pain may also experience stress, crying and prolonged hospitalisation. Clown intervention is a promising nonpharmacological intervention. However, studies on the effectiveness of clown intervention in pain management have reported conflicting findings. Objective: To evaluate the effectiveness of clown intervention in relieving pain in children, as well as its effects on cortisol levels, crying duration and length of hospital stay. Design: Systematic review and meta‐analysis of randomised controlled studies. Data sources: PubMed, Web of Science (SCI), Embase, PsycINFO, the Cochrane Library, Chinese National Knowledge Infrastructure (CNKI), Weipu (VIP), Wanfang Data and SinoMed were systematically searched from inception date to December 31, 2020. Review methods: Two reviewers independently used the Cochrane risk of bias tool to assess the risk of bias of the included studies. Meta‐analysis was conducted when data were available, otherwise, a narrative description was provided. Data were analysed using Review Manager 5.3. The review process is reported according to PRISMA. Results: Nine studies including 852 children met the inclusion criteria. The results showed that compared with standard care, clown intervention was beneficial for relieving pain. Further subgroup analysis showed that it was more effective with children aged 2–7 years. The duration of crying after the procedure and the length of stay were shortened, but there was no significant difference in cortisol levels. Conclusion: Clown intervention may be a promising way to relieve acute pain in children, especially those aged 2–7 years. It also seems to shorten the duration of crying and the length of hospital stays, but the effect on cortisol levels is still uncertain. More high‐quality randomised controlled trials are needed to confirm these results and take into account different age groups, cultural backgrounds and specific populations.